Partial orders based on the CS decomposition - Xu, S. Z.; Chen, J. L.; Benítez, J. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 512.5 A new decomposition for square matrices is given by using two known matrix decompositions, a new characterization of the core-EP order is obtained by using this new matrix decomposition. Also, we will use a matrix decomposition to investigate the minus, star, sharp and core partial orders in the setting of complex matrices.